2009
DOI: 10.1212/01.wnl.0000327339.55844.1a
|View full text |Cite
|
Sign up to set email alerts
|

Effect of atorvastatin in elderly patients with a recent stroke or transient ischemic attack

Abstract: There was no heterogeneity in the stroke reduction seen with atorvastatin in the elderly and younger groups. Cardiac events and revascularization procedures were also lower in both the elderly and younger subgroups treated with atorvastatin. These results support the use of atorvastatin in elderly patients with recent stroke or TIA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0
3

Year Published

2009
2009
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 22 publications
1
64
0
3
Order By: Relevance
“…Furthermore, the favorable benefit of atorvastatin was observed in the young and elderly, in men and women, and across ischemic stroke subtype at entry. [61][62][63] A finding of note in SPARCL was the association of statin treatment with a higher incidence of hemorrhagic stroke (n=55 [2.3%] for statin treatment versus n=33 [1.4%] for placebo; HR, 1.66; 95% CI, 1.08-2.55). 64 A similar observation was seen in the subset of 3200 patients who had stroke before randomization in the Heart Protection Study (HPS), in which there was a 91% relative rise in risk of hemorrhagic stroke in patients assigned to statin treatment.…”
Section: Dyslipidemiamentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the favorable benefit of atorvastatin was observed in the young and elderly, in men and women, and across ischemic stroke subtype at entry. [61][62][63] A finding of note in SPARCL was the association of statin treatment with a higher incidence of hemorrhagic stroke (n=55 [2.3%] for statin treatment versus n=33 [1.4%] for placebo; HR, 1.66; 95% CI, 1.08-2.55). 64 A similar observation was seen in the subset of 3200 patients who had stroke before randomization in the Heart Protection Study (HPS), in which there was a 91% relative rise in risk of hemorrhagic stroke in patients assigned to statin treatment.…”
Section: Dyslipidemiamentioning
confidence: 99%
“…797 By contrast, trials of medical therapies such as statins have included relatively large numbers of elderly patients with CAD or recent stroke and support safety and event reduction in these groups, although further study in the elderly may still be needed. 62,[798][799][800] Recent data from GWTG-Stroke show substantial temporal improvements in measures of stroke care performance from 2003 to 2009 in each 10-year age group >50 years, and many age-related treatment gaps were narrowed or eliminated over time. These and data from other systems suggest that age-related disparities in hospital-based care for stroke may be decreasing over time.…”
Section: Identifying and Responding To Populations At Highest Riskmentioning
confidence: 99%
“…31 An analysis of the entire SPARCL cohort , using an intention to treat protocol, compared primary and secondary endpoints between patients over 65 and under 65 years old. 32 Patients over 65 were more likely to have hypertension, a history of carotid stenosis at baseline, and less likely to be current smokers compared with younger patients. 32 For the primary endpoint there was a 10% RRR (HR 0.90, 0.73-1.11, P = 0.33) in the elderly group compared to a 26% RRR in the younger group (HR 0.74, 0.57-0.96, P = 0.02).…”
Section: Dovepressmentioning
confidence: 93%
“…An analysis of two groups of patients, one receiving statin treatment at the time of discharge, while the As described above, there is controversy over whether statin therapy is effective for preventing stroke in primary and secondary prevention for elderly patients with CAD; however, for elderly Japanese in whom stroke frequently occurs, an increasing number of studies have suggested that decreased LDL-C levels resulting from statin therapy are associated with a decreased risk of stroke in both male and female primary prevention patients with hyper-LDL cholesterolemia. Meanwhile, regarding the prevention of events after stroke or TIA, a sub-analysis of the SPARCL study showed that statins are effective for preventing stroke, TIA and major cardiovascular events in the elderly, similar to non-elderly adults 48) . Although there have been no results indicating that statins are effective for preventing recurrence after cerebrovascular disease in Japanese patients, statin therapy should also be considered in the elderly to prevent the recurrence of cerebral infarction.…”
Section: ) the Efficacy For Preventing Cadmentioning
confidence: 99%